2021
DOI: 10.1177/20416695211054534
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual Grasping Adheres to Weber's Law

Abstract: Weber's law states that our ability to detect changes in stimulus attributes decreases linearly with their magnitude. This principle holds true for many attributes across sensory modalities but appears to be violated in grasping. One explanation for the failure to observe Weber's law in grasping is that its effect is masked by biomechanical constraints of the hand. We tested this hypothesis using a bimanual task that eliminates biomechanical constraints. Participants either grasped differently sized boxes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Here we found that actions obey Weber's law. The SD of the final inter-finger separation increased as a function of the inter-target distance, with a slope ranging from 0.012 to 0.038, in line with the classic and modern literature on Weber's law (e.g., Bhatia et al, 2022;Derzsi & Volcic, 2023;Fechner, 1860;Hesse et al, 2021;McKee & Welch, 1992;Teghtsoonian, 1971).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Here we found that actions obey Weber's law. The SD of the final inter-finger separation increased as a function of the inter-target distance, with a slope ranging from 0.012 to 0.038, in line with the classic and modern literature on Weber's law (e.g., Bhatia et al, 2022;Derzsi & Volcic, 2023;Fechner, 1860;Hesse et al, 2021;McKee & Welch, 1992;Teghtsoonian, 1971).…”
Section: Discussionsupporting
confidence: 83%
“…When this non-linear scaling is appropriately considered, Weber's law can be detected even in grasping movements. Moreover, when other variables than MGA are considered, Weber's law is regularly observed (e.g., Derzsi & Volcic, 2023;Hesse et al, 2021). For instance, Derzsi and Volcic (2023) found that to achieve stable grasps on differently sized objects the SD of grasp contact positions increases as a function of object size, coherently with Weber's law.…”
Section: Discussionmentioning
confidence: 81%
“…All these factors should have, if anything, favored the emergence of the perception-action dissociation. The range of sizes used for our objects was also not critical as similar ranges have been already used to study Weber’s law (Ganel et al, 2017; Hesse et al, 2021).…”
Section: Discussionmentioning
confidence: 99%